Assessment of diagnostic value of cytological examination in lung carcinoma in own material obtained by EBUS and EUS methods - Wiśniewski, Piotr; Głogowski, Maciej; Olszewski, Włodzimierz (Polish Journal of Pathology, 2018)
The aim of the study was the evaluation of the efficiency of cytological examination of the material obtained by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) and endoscopic ultrasound bronchoscope-guided fine needle aspiration (EUSB-FNA) methods in the diagnosis of lung carcinoma. The usefulness was also assessed of the material obtained in that way for immunocytochemical and molecular tests in the diagnosis of non-small cell lung carcinoma. The material included cytological preparations obtained by EBUS and EUS methods. It was demonstrated that the technique made it possible to obtain diagnostic material from 94% of patients. A retrospective thorough analysis of those cases was the basis for the discussion of diagnostic difficulties.